Influence of pH on the biodegradation efficiency of fats, oils,and grease by biosurfactant‑producing bacterial consortia - Wong, Jia Ying; Ngieng, Ngui Sing; Awang Ahmad Sallehin, Awang Husaini; Rosmawati, Saat; Hasnain, Hussain (Springer Nature, 2025)
The accumulation of fats, oils, and grease (FOG) in wastewater systems presents major environmental challenges, necessitating the development of effective bioremediation strategies. Bio surfactant producing bacteria are promising for FOG degradation; however, their efficacy is highly pH-dependent, affecting microbial metabolism and bio surfactant stability. This study evaluates the impact of pH on FOG biodegradation by locally isolated bio surfactant producing bacterial consortia to identify optimal pH conditions. Two highly efficient biosurfactant-producing bacterial isolates, identified via 16S rRNA sequencing as Pseudomonas aeruginosa and Bacillus velezensis, were cultured in Bushnell Haas (BH) medium to form a bacterial consortium. The consortium was then inoculated into fresh BH medium, adjusted to pH values from 4 to 9, and supplemented with 1% FOG (w/v). Samples were monitored at six-day intervals for 30 days under continuous shaking at 130 rpm. After 30 days of biodegradation, the solid FOGs in pH 6 disappeared while flocs were observed in both pH 4 and 5. Despite greater floc formation at pH 6, GC–MS analysis revealed that pH 4 achieved the highest degradation rate, displaying the fewest FOG peaks and the lowest area under peaks, indicating the most substantial FOG reduction. Notably, the consortium achieved the highest FOG removal at pH 4, an acidic condition under which most long-chain FOG components were completely degraded or transformed into shorter chains. This finding reveals an unexpected optimum pH 4 for FOG bioremediation by two efficient biosurfactant-producing bacteria combined into a synergistic consortium, highlighting a potential strategy to enhance grease waste treatment.